Implementasi Pelatihan Tari Nusantara dalam Meningkatkan Nasionalisme dan Kesadaran Budaya - Mulyani, Aan; Izzati, Umi Anugerah; Bachria, Bachtiar Syaiful (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2024)
The study attempts to present a qualitative description about how Nusantara dance training may serve to develop nationalism and cultural awareness. That shall be accomplished via a systematic review method and presented in a qualitative descriptive manner. This research uses a systematic review process that includes a number of phases: (a) creating research questions, (b) performing a literature search, (c) performing screening and selection of research articles, (d) carrying out analysis and synthesis of qualitative findings, (e). This research indicates that dance training can be considered a process that gives support and knowledge to dance creators when creating a new movement that incorporates distinctive characteristics with the creator's creativity, and maintaining the distinctive characteristics of every person's movement. The success of the training is dependent to an approach and model that best corresponds to the creator's Key words: Training Implementation, Nusantara Dance, Nationalism, Cultural Awareness